2003
DOI: 10.1124/mol.63.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effect of Phosphorylated Metabolites of Anti-Human Immunodeficiency Virus and Anti-Hepatitis B Virus Pyrimidine Analogs on the Behavior of Human Deoxycytidylate Deaminase

Abstract: Deoxycytidylate deaminase, catalyzing the conversion of dCMP to dUMP, is an important enzyme in the de novo synthesis of thymidine nucleotides. It also may be involved in the action, as well as the metabolism of anticancer agents. Recently, several L-and D-configuration pyrimidine deoxynucleoside analogs were found to be potent antiviral and antitumor agents. Their interaction with dCMP deaminase as a monophosphate or a triphosphate metabolite is not clear. These include D-nucleoside analogs such as-fluorocyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Enzymatic studies with purified human DCTD showed that this enzyme is capable of deaminating PSI-6130-MP to RO2433-MP. This enzyme is believed to be involved in regulating the intracellular concentrations of dCTP and dTTP for DNA synthesis, as the enzyme is activated in the presence of dCTP and is inhibited by dTTP (13,17). Our enzyme kinetic study was performed in the absence of any activators or inhibitors for comparison reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Enzymatic studies with purified human DCTD showed that this enzyme is capable of deaminating PSI-6130-MP to RO2433-MP. This enzyme is believed to be involved in regulating the intracellular concentrations of dCTP and dTTP for DNA synthesis, as the enzyme is activated in the presence of dCTP and is inhibited by dTTP (13,17). Our enzyme kinetic study was performed in the absence of any activators or inhibitors for comparison reasons.…”
Section: Discussionmentioning
confidence: 99%
“…gram-negative bacteria Escherichia coli and Salmonella typhimurium, dUMP is synthesized via two steps, namely, the deamination of deoxycytidine-5′-triphosphate (dCTP) to deoxyuridine-5′-triphosphate (dUTP) by dCTP deaminase and the subsequent hydrolysis of dUTP to dUMP by dUTPase. Interestingly, dCD reduces the efficiency of anticancer and antiviral drugs via deamination at the nucleotide level 3,4 ; this indicates that dCD inhibitors have potential applications in chemotherapy.…”
Section: Introductionmentioning
confidence: 98%
“…Viral polymerases incorporate l -derivatives more readily than do the human ones (20–21). Nucleoside degrading enzymes, such as nucleoside deaminases and phosphorylases, tend to be strictly selective for d -nucleotides although only limited data is available (11,22). The lack of degradation of l -nucleosides has however been demonstrated in mice, where l -nucleosides were gradually excreted in the unchanged form following intraperitoneal administration (5).…”
Section: Introductionmentioning
confidence: 99%